Building Future-Ready Societies with Human Values: Refactoring Education - Rathinasamy, Durga (Global journal of Business and Integral Security, 2026)
As the world navigates the twin transitions toward a digital and green economy, there is an urgent need to root the future in universal human values. “Building Societies with Human Values Refactoring”, developed by Sathya Unar Charitable Trust, is a grassroots education model that re-engineers character, citizenship, and sustainability consciousness among youth. The curriculum is adaptable across age groups and program durations, bridging the value gap in education by cultivating empathy, responsibility, and resilience. Structured around a developmental flow from “Self → Society → Sustainability,” the curriculum integrates introspection, journaling, storytelling, and project-based learning with self-reflection.Modules such as “Self-discovery”, “Sustainable Relationship management”, “Mindful morality in socio-digital ecosystems”, “Human-Nature Integration”, “Financial Management”, and many more guide learners through deeply personal and social inquiries. The capstone involves real-world field immersion and community engagement, enabling learners to translate inner transformation into social contribution and sustainable futures.